Предмет: Алгебра,
автор: markovssava08
Ещё раз задаю вопрос.
Приложения:
Ответы
Автор ответа:
1
Ответ:
ответ будет 3
объяснение
larisaserova53:
Я скинула решение, смотри в своём профиле
Автор ответа:
0
( 3^48 - 3^47 + 17 *3^46 ) / 23 * 27^15 = 3^46 ( 3^2 -3 +17 ) / 23 * 27^15 =
= 3^46 * 23 / 23*27 ^15 = 3^46 / 27^15= 3^46 / 3^45 =3
= 3^46 * 23 / 23*27 ^15 = 3^46 / 27^15= 3^46 / 3^45 =3
Похожие вопросы
Предмет: Русский язык,
автор: помогите487
Предмет: Русский язык,
автор: владислав251
Предмет: Русский язык,
автор: lork2005
Предмет: Математика,
автор: gggggggggguyyy
Предмет: Физика,
автор: taceguk